"A Curious Epitome of the Life of the City": New York, Broadway, and the Evolution of the Longitudinal View. (September 2018) - Yablon, Nick
Discussions of urban representation have been hampered by a persistent contrast between the view from above and the view from street level, or between the urban planner's panoptic gaze and the flâneur's fleeting glance. This article challenges such contrasts by identifying a third way of representing a city, that of moving block-by-block along the length of its main thoroughfare. It traces the emergence of what it calls the "longitudinal view" back to antebellum New York, when tour guides and urban sketches promoted the "walk up Broadway" as a means to encompass the social and functional diversity of the expanding metropolis, and when visual genres such as the moving panorama and the pictorial directory offered a virtual simulation of that journey—one that echoed the perpendicular perspective of an omnibus passenger. It concludes by exploring the subsequent appropriation of the longitudinal view by artists, photographers, and filmmakers.